Antioxidant activity analysis of new interspecific hybrid germplasm thyme and oregano essential oils with different chemotypes - Meiyu Sun; Jiahui Miao; Yanan Zhang; Yuanpeng Hao; Jinzheng Zhang; Hui Li; Hongtong Bai; Lei Shi (BMC Plant Biology)
Abstract Thyme and oregano essential oils (EOs) and their components have numerous applications in the pharmaceutical, food, and cosmetic industries owing to their antioxidant, antibacterial, antifungal, anti-inflammatory, antiviral, and immunological properties. We attempted to create new chemotypes through the hybridization of thyme and oregano for functional EO research and product development. Here, we used interspecific hybridization to create new thyme and oregano germplasms with new EO chemotypes. The antioxidant activities of these new chemotype EOs were verified by DPPH, ABTS, and FRAP analyses. We determined that there are five types of thyme hybrid EOs: geraniol-type, carvacrol-type, thymol-type, parent polymerization-type, and α-terpineol/α-terpinyl acetate-type. Moreover, there are five types of oregano hybrid EOs: carvacrol-type, thymol-type, sabinene hydrate-type, parent polymerization-type, and carvacrol/sabinene hydrate-type. The geraniol, thymol, and carvacrol contents ranged from 30.45%, 1.21% and 0.00%, respectively, in the parents to 81.66%, 52.65%, and 46.16%, respectively, in the thyme hybrids. The carvacrol and thymol contents ranged from 2.33% to 24.18%, respectively, in the parents to 94.16% and 76.77%, respectively, in the oregano hybrids, indicating obvious heterosis. We further used three antioxidant assays, DPPH, ABTS, and FRAP, to analyse the antioxidant activity of thyme and oregano hybrid EO samples. The antioxidant capacities of carvacrol- and thymol-type EOs were significantly superior to those of other chemotypes. Our data suggest that carvacrol- and thymol-type EOs with greater antioxidant potential can be applied in many industries. In addition, the function of high geraniol-type thyme EO should be further researched. The results will also be very useful for the selection of new varieties, functional research on carvacrol-, thymol-, and geraniol-type essential oils, and product development of feed additives, cosmetics, etc.